DEVELOPMENT OF AUGMENTED REALITY FLASHCARD MEDIA TO IMPROVE LITERACY AND SHORT STORY WRITING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Latifah Dwi Utami; Gunawan Gunawan (SOSIOEDUKASI, 2026)
This study aims to develop Augmented Reality Flashcard media that meets the level of feasibility, practicality, and effectiveness in improving reading literacy skills and short story writing skills in elementary school students. The method used is research and development (R&D) with a 4D model (define, design, develop, and disseminate). The research subjects are grade II students of UMP elementary school. Quantitative research involves an experimental group and a control group. Data collection techniques consist of tests, questionnaires, interviews, observations, and documentation. Data analysis applied statistical normality, homogeneity, and independent sample test. The validation results showed that the media produced was considered feasible and practical to be applied in the learning process. The effectiveness test through the t-test obtained a significance value of 0.000 (<0.05) on literacy ability to read and write short stories, indicating a significant difference between the two groups. The results of the evaluation showed that the average score of students in the experimental class was higher than in the control class. The use of Augmented Reality Flashcards is effective in improving students' literacy skills and short story writing skills. Therefore, Augmented Reality Flashcards can be used as an alternative innovative learning media that supports the improvement of literacy skills at the elementary school level.